Kino pod presją - HENDRYKOWSKI, MAREK (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2016)
Cinema under pressure The article contains a synthetic look at the issue of film censorship, taking into account its various forms. The author combines the perspective of a contemporary synchronous with the diachronic perspective, dating back to the distant origins of cinema and filmmaking, in conjunction with politics and ideology.